Tindak Kekerasan dalam Novel Elgara karya Lusiafriaa: Kajian Sosiologi Sastra - Syafriania, Herni Harpin; Hayati, Yenni (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to determine the form of violence in the novel Elgara by Lusiafriaa, the factors that cause violence in the novel Elgara by Lusiafriaa, and the impact of violence in the novel Elgara by Lusiafriaa. The theory in this research is literary sociology theory. This research is a qualitative research using descriptive method. The data source of this research is the novel Elgara by Lusiafriaa. The steps taken in collecting data for this research are reading and understanding the novel Elgara by Lusiafriaa, identifying the main and additional characters in the novel Elgara by Lusiafriaa, looking for and recording events that describe violence in the novel Elgara by Lusiafriaa, inventorying data on violence in the novel Elgara by Lusiafriaa. The validation technique used in this research is triangulation technique. The data analysis technique in this study is to classify the data based on the speech/actions or thoughts of the characters and narrators related to the forms of violence, factors causing violence, and the impact of violence, analyze (interpretation) the data, conclude the results of data analysis, and write a report. The results of this study are forms of violence consisting of physical violence and psychological violence. Factors causing violence consisting of individual factors and social factors. The impact of violence consists of physical impact, psychological impact, and social impact.